Polymorphism in INSR Locus Modifies Risk of Atrial Fibrillation in Patients on Thyroid Hormone Replacement Therapy - Soto-Pedre, Enrique; Siddiqui, Moneeza K.; Maroteau, Cyrielle; Dawed, Adem Y.; Doney, Alex S.; Palmer, Colin N. A.; Pearson, Ewan R.; Leese, Graham P. (Frontiers in Genetics, 2021)
Aims: Atrial fibrillation (AF) is a risk for patients receiving thyroid hormone replacement therapy. No published work has focused on pharmacogenetics relevant to thyroid dysfunction and AF risk. We aimed to assess the effect of L-thyroxine on AF risk stratified by a variation in a candidate gene. Methods and results: A retrospective follow-up study was done among European Caucasian patients from the Genetics of Diabetes Audit and Research in Tayside Scotland (GoDARTS) cohort (Scotland, UK). Linked data on biochemistry, prescribing, hospital admissions, demographics and genetic biobank were used to ascertain patients on L-thyroxine and diagnosis of AF. A GWAS-identified insulin receptor-INSR locus (rs4804416) was the candidate gene. Cox survival models and sensitivity analyses by taking competing risk of death into account were used. Replication was performed in additional sample (The Genetics of Scottish Health Research register- GoSHARE), and meta-analyses across the results of the study and replication cohorts were done. We analysed 962 exposed to L-thyroxine and 5,840 unexposed patients who were rs4804416 genotyped. The rarer G/G genotype was present in 18% of the study population. The total follow-up was up to 20 years, and there was a significant increased AF risk for patients homozygous carriers of the G allele exposed to L-thyroxine (RHR=2.35, P=1.6e-02). The adjusted increased risk was highest within the first three years of exposure (RHR=9.10, P=8.5e-04). Sensitivity analysis yielded similar results. Effects were replicated in GoSHARE (n=3,190). Conclusions: Homozygous G/G genotype at the INSR locus (rs4804416) is associated with an increased risk of AF in patients on L-thyroxine, independent of serum of free thyroxine and thyroid-stimulating hormone serum concentrations.